PRINSIP DAN PENDEKATAN PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Rinja Efendi; Tasya Sri Ratu; Shinta Maharani; Sinta; Widian Mulyani; Dwi Arzeti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the principles and approaches to Indonesian language learning in elementary schools and analyze the obstacles encountered in their implementation. This research employed a descriptive qualitative approach with a case study method at SDN 002 Rambah Samo. Subjects included teachers, fourth-fifth grade students, and the principal. Data collection techniques included semi-structured interviews, observation, and document analysis. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and verification. The results indicate that the applied learning principles include communicative, contextual, integrative, and student-centered principles. The dominant learning approaches used were the scientific and thematic integrative approaches, which foster student activeness and engagement in the learning process. However, several obstacles were encountered in its implementation, such as low student self-confidence, differences in learning abilities, limited learning media, and teachers' tendency to use the lecture method. The implementation of these principles and approaches has led to active and meaningful learning and contributed to improving students' critical thinking skills, although not yet optimal. Therefore, it is necessary to develop more innovative, interactive, and media-based learning methods so that the learning process becomes more effective and appropriate to the needs of students in elementary schools.